Angels : A Very Short Introduction - Jones, David Albert (New York Oxford University Press, 2011)
What are angels? Where were they first encountered? Can we distinguish angels from gods, fairies, ghosts, and aliens? And why do they remain so popular? This Very Short Introduction investigates stories and speculations about angels in religions old and new, in art, literature, film, and the popular imagination.
Include Index
Keywords: Angels in Popular Culture -- Angels -- Angels in Art -- Angels in Literature